MODIFIKASI SISTEM OPERASI FIXED–BED GASIFIERSEKAM PADI PT. NATIONAL CHAMPIGNON - Bambang Suwondo Rahardjo; Taufik Yuwono; Maria Harsitorukmi (Jurnal Energi dan Lingkungan (Enerlink), 2011)
Installation of O2 and steam injection system inside gasifier can be expected to improve syngas quality, all at once N2 content is decreasing, with the result of H2/CO ratio >1 that will produced liquid product optimally. The mixed air+steam injection by steam valve variation opening of ¼ as well as ½ rotation still being possible gasifier operation at temperature condition higher than 700oC. Mixed air+steam injection showed more easily flameable than air injection only, so this mean H2content in the syngas will be increasing. Kata kunci:modification of systems, fixed bed gasifier, gasification, rice husk, synthetic gas